Logic programming, knowledge representation, and nonmonotonic reasoning essays dedicated to Michael Gelfond on the occasion of his 65th Birthday - Son, Tran Cao.; Balduccini, Marcello; SpringerLink (Online Service). (Berlin Heidelberg Springer, 2011)
This Festschrift volume, published in honor of Michael Gelfond on the occasion of his 65th birthday, contains a collection of papers written by his closest friends and colleagues. Several of these papers were presented during the Symposium on Constructive Mathematics in Computer Science, held in Lexington, KY, USA on October 25-26, 2010. The 27 scientific papers included in the book focus on answer set programming. The papers are organized in sections named Foundations- ASP and Theories of LP, KR, and NMR, ASP and Dynamic Domains, and ASP Applications and Tools.
Opening - Homage to Michael Gelfond on His 65th Birthday.- Foundations ASP and Theories of LP, KR, and NMR Answer Set Programming's Contributions to Classical Logic An Analysis of ASP Methodology.- Closure and Consistency Rationalities in Logic-Based Argumentation.- Manifold Answer-Set Programs and Their Applications.- On the Minimality of Stable Models.- Challenges in Answer Set Solving.- Exploring Relations between Answer Set Programs.- Compact Translations of Non-disjunctive Answer Set Programs to Propositional Clauses.- Effectively Reasoning about Infinite Sets in Answer Set Programming.- Inspecting Side-Effects of Abduction in Logic Programs.- Argumentation and Answer Set Programming. Interlude- Cantors Paradise Regained- Constructive Mathematics from Brouwer to Kolmogorov to Gelfond.- Interlude- Recollections on Michael Gelfonds 65th Birthday.- ASP and Dynamic Domains- Evolving Logic Programs with Temporal Operators.- On Representing Actions in Multi-agent Domains.- Nonmonotonic Multi-Context Systems- A Flexible Approach for Integrating Heterogeneous Knowledge Sources.- Perspectives on Logic-Based Approaches for Reasoning about Actions and Change.- Refinement of History-Based Policies.- Translating General Game Descriptions into an Action Language.- Revisiting Epistemic Specifications.- Interlude- Answer Set, Programming.- Interlude- Michael Gelfond- Essay in Honour of His 65th Birthday.- ASP Applications and Tools- PLINI- A Probabilistic Logic Program Framework for Inconsistent News Information.- ASP as a Cognitive Modeling Tool- Short-Term Memory and Long-Term Memor.- A Temporally Expressive Planner Based on Answer Set Programming with Constraints- Preliminary Design.- Applications of Answer Set Programming in Phylogenetic Systematics.- ASP at Work- Spin-off and Applications of the DLV System.- Combining Answer Set Programming and Prolog- The ASP PROLOG System.- On the Practical Side of Answer Set Programming.- ASTREA- Answer Sets for a Trusted Reasoning Environment for Agents.- Ending- Tea Times with Gelfond
Electronic reproduction.
Keywords: Gelfond, Michael -- Congresses; Logic programming -- Congresses; Computer science -- Mathematics -- Congresses; Knowledge representation (Information theory) -- Congresses; Electronic books